SOCIO-ECONOMIC ASPECT OF RIGHT TO EDUCATION ACT - KUMAR, NAVEEN (THE PRIMARY TEACHER, 2013)
Education is core to development. So far as economic development of an individual or a society is concerned, it is largely determined by the quality of educational outcomes. The quality of societal development (standard and quality of life) depends essentially on the number and quality of educated people (Trapero, 1985). A number of researches reveal that cognitive development of a child largely occurs during the age of 3 to 8. So, preprimary and primary schooling age has been considered to be the most crucial for overall development of any child. In the pre-school years, children understand themselves as individuals; in addition, they understand themselves as part of a social world